Schizophrenia and oxidative stress from the perspective of bibliometric analysis - Chen, Meng-Yi; Zhang, Qinge; Liu, Yu-Fei; Zheng, Wan-Ying; Si, Tong Leong; Su, Zhaohui; Cheung, Teris; Jackson, Todd; Li, Xiao-Hong; Xiang, Yu-Tao (Frontiers in Psychiatry, 2023)
Background: A growing number of studies has implicated oxidative stress in the pathophysiology of psychiatric disorders including schizophrenia. The aim of this study was to explore the field of schizophrenia and oxidative stress-related research from a bibliometric perspective. Methods: All relevant publications on schizophrenia and oxidative stress were obtained from Web of Science Core Collection (WOSCC) database from its inception date to November 8, 2022. VOSviewer software was used to examine co-authorships and co-occurring keywords. R software was used to present the main characteristics of publications, cooperation frequency among countries and three-field plots. CiteSpace was used to investigate keywords with the strongest citation bursts. Results: A total of 3,510 publications on schizophrenia and oxidative stress were included. The United States had the largest number of publications (26.1%), and international collaborations. University of Melbourne was the most productive institution, while Schizophrenia Research was the most productive journal in this field. Apart from “schizophrenia” and “oxidative stress”, the terms “prefrontal cortex”, “brain” and “nitric oxide” were among the most frequently used keywords. Conclusions: In conclusion, research on the association between oxidative stress and schizophrenia has received growing attention in the academic literature that is expected to continue its upward trajectory during the next two decades. Existing research suggests there has been a transition from research focused on pathways to animal models, and subsequently to clinical applications. Intervention studies on oxidative stress and schizophrenia are likely to be an important focus of related work in the near future.